The Implementation of Sharia Contracts in Cooperative Management (A Study at Darul Mukhlisin Islamic Boarding School) - Ulya Syafrina Saragih; Muhammad Zuhirsyan; Asmalidar; Viana Fadhila (Universitas Serambi Mekkah, 2024)
The purpose of this study is to assess the implementation of a cooperative institution management based on Sharia contracts within Islamic boarding schools, where, in essence, Islamic boarding schools are suitable for implementing various Sharia principles as Islamic educational institutions. This research employs a qualitative approach that is descriptive, analytical, and inductive in nature, aiming to unearth fundamental aspects of the phenomenon, reality, and experiences through data collection methods such as interviews, observations, and documentation. The research findings indicate that cooperative management can be carried out within Islamic boarding schools by empowering various Sharia contracts that have been legalized by the DSN MUI, such as Murabahah, Kafalah bil Ujrah, Qardhul Hasan, Salam, and Mudharabah contracts.